Negative effect of seasonal heat stress on testis morphology and transcriptomes in Angora rabbit - Haisheng Ding; Yuanlang Wang; Huiling Zhao; Jinzi Wang; Dongwei Huang (BMC Genomics)
Abstract Background The temperature of testes exposed to hyperthermic conditions can affect livestock reproductive performance. This study aimed to explore the difference in semen quality, testicular morphological structure, and gene expression profiles of testes of Angora rabbits in spring (no heat stress), summer (intense heat stress), and autumn (no heat stress) seasons. Results Heat stress during summer significantly reduced semen quality and damaged testicular morphology and spermatogenesis, which recovered to normal levels in autumn, although semen quality recovery was notably slow. RNA-Seq analysis showed that the expression levels of 8703 genes changed significantly in summer, but their expression levels in autumn returned to those in spring, which was consistent with the testicular morphology analysis results in different seasons. Enrichment analysis revealed that the DEGs were primarily associated with spermatogenesis, sperm motility, spermatid development, cell death, regulation of apoptotic processes, and responses to external stimuli. The MAPK, Rap1, TNF, Ras, Apoptosis, and Wnt signaling pathways regulated reproduction under heat stress. In addition, minimal variations in testicular morphology and gene expression profiles were observed between autumn and spring. Gene expression pattern analysis showed that genes with high expression in summer mainly participated in the regulation of cell apoptosis, immunity, and response to heat stress, whereas genes with low expression in summer mainly participated in the regulation of spermatogenesis. Conclusions This study investigated the influence of different seasons on the reproductive performance of male Angora rabbits and provided initial insights into the molecular regulatory mechanisms underlying the testicular response to heat stress during summer.